Idiopathic polypoidal choroidal vasculopathy in thai patients with clinical and angiographic choroidal neovascularization - Bhoomibunchoo C. (2017)
© 2017 Bhoomibunchoo et al. Objective: This study aimed to study the prevalence and characteristics of idiopathic polypoidal choroidal vasculopathy (IPCV) in Thai patients with clinical and angiographic choroidal neovascularization (CNV). Patients and methods: A consecutive case study of 140 patients presenting with CNV was conducted in nine large referral eye centers throughout Thailand. The demographic data, fundus photographs, fundus fluorescein angiography and indocyanine green angiography of the patients were analyzed. Results: Of 129 patients with clinical and angiographic CNV, IPCV was diagnosed in 100 patients (77.52%), idiopathic CNVs in 16 patients (12.40%) and age-related macular degeneration (AMD) in 12 patients (9.30%). Of the 107 eyes with IPCV, 90 eyes (84.11%) had both branching venous networks (BVNs) and polypoidal lesions. Most IPCV patients (93%) had unilateral involvement and were at a younger age than AMD patients. In all, 79 eyes (73.83%) had lesions found in the macular area, 14 eyes (13.08%) in the temporal to vascular arcades, ten eyes (9.35%) in the peripapillary area and four eyes (3.74%) in both macular and peripapillary areas. The clinical manifestations of IPCV at presentation were categorized into two patterns. There were 95 eyes (88.79%) of a hemorrhagic pattern and 12 eyes (11.21%) of an exudative pattern. Conclusion: IPCV is the most common macular disease in Thai patients with CNV. Most IPCVs have both BVNs and polypoidal lesions located in the macular area and present with a hemorrhagic pattern.